Extending multimedia languages to support multimodal-multiuser interactions - Guedes, Álan L. V.; Barbosa, Simone D. J. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2019)
Hardware and software technologies have given rise to a new class of human-computer interfaces that both explores multiple modalities and allows for multiple collaborating users. When compared to the development of traditional single-user WIMP (windows, icons, menus, pointer)-based applications, however, applications supporting the seamless integration of multimodal-multiuser interactions bring new specification and runtime requirements. In this thesis, with the aim of assisting the specification of multimedia applications that integrate multimodal-multiuser interactions, we: (1) propose the MMAM (Multimodal-Multiuser Authoring Model); (2) present three different instantiations of it (in NCL, HTML, and a block-based syntax); and (3) evaluate the proposed model through a user study. MMAM enables programmers to design and ponder different solutions for applications with multimodal-multiuser requirements. Its instantiations served as proofs of concept about the feasibility of our model and enabled us to perform the user study. The user study focused on capturing evidence of both the user understanding and the user acceptance of the proposed model. 94.47% of the participants gave positive answers to the block-based representation TAM questions, whereas 75.17% of them gave positive answers to the instantiations-related questions.